Cortical thickness increases after simultaneous interpretation training. (April 2017) - Hervais-Adelman, Alexis; Moser-Mercer, Barbara; Murray, Micah M.; Golestani, Narly
Abstract: Simultaneous interpretation is a complex cognitive task that not only demands multilingual language processing, but also requires application of extreme levels of domain-general cognitive control. We used MRI to longitudinally measure cortical thickness in simultaneous interpretation trainees before and after a Master's program in conference interpreting. We compared them to multilingual control participants scanned at the same interval of time. Increases in cortical thickness were specific to trainee interpreters. Increases were observed in regions involved in lower-level, phonetic processing (left posterior superior temporal gyrus, anterior supramarginal gyrus and planum temporale), in the higher-level formulation of propositional speech (right angular gyrus) and in the conversion of items from working memory into a sequence (right dorsal premotor cortex), and finally, in domain-general executive control and attention (right parietal lobule). Findings are consistent with the linguistic requirements of simultaneous interpretation and also with the more general cognitive demands on attentional control for expert performance in simultaneous interpreting. Our findings may also reflect beneficial, potentially protective effects of simultaneous interpretation training, which has previously been shown to confer enhanced skills in certain executive and attentional domains over and above those conferred by bilingualism. Highlights: We carried out a longitudinal investigation on simultaneous interpretation training. Trainee interpreters showed cortical thickening in multiple regions. These regions are implicated in audio-motor and phonological processing. Thickening was also seen in regions linked to executive and attentional control. Interpreter training may also confer some protection against normal, age-related thinning.